Juridical Review of Spatial Planning and Control of Space Utilization in the Situ Kayu Antap Area in the South Tangerang City Area in the Perspective of National Land Law - Levy Maulana Muhammad (Faculty of Law, Universitas Pekalongan, 2023)
Juridically, there is a legal problem where Situ Kayu Antap located in the city of South Tangerang has a discrepancy in the use of its space, namely the issuance of land rights without the results of analysis or study of relevant physical data and juridical data, so it is necessary to control the use of space in the situ area in the South Tangerang city area in the perspective of national land law. The type of research in this research is normative legal research, namely research on legal principles, legal theory, legal concepts and legislation related to this research. The theory, principles and legal concepts are used to determine that the location of Situ Kayu Antap is an inland water source in the South Tangerang city area which is designated as one of the National Strategic Areas and is a protected area that must be preserved for the welfare of the people. Based on the author's research, PT. Hana Kreasi Persada, which currently has a Building Use Right over the Situ Kayu Antap area, can have its land rights revoked on the basis of public interest and can be compensated by the South Tangerang city government based on the provisions of the applicable laws and regulations.